Are Motor and Cognitive Control, Impulsivity and Risk-Taking Behaviour as Well As Moral Decision Making Determined by the Activity of Prefrontal Cortex during Stroop Test? - Albertas Skurvydas; Dovilė Valančiene; Andrius Šatas; Dalia Mickevičiene; Kazys Vadopalas; Diana Karanauskienė (Lithuanian Sports University, 2018)
Background. The main aim of our research was to determine if there was a relationship between prefrontal cortex activity during Stroop test (dependent variables) and variables of "Go/NoGo", Balloon Analogue Risk Task, impulsivity score, diﬀerent tests of cognitive functions, moral decisions tests (altruistic or egoistic), Fitts-like motor control task, fve character traits, emotional intelligence, mood, sleepiness and perceived stress, total physical activity of subjects (independent variables). Methods.In total, 20 undergraduate students (mean age were 21.3, SD = 1) met the criteria and agreed to participate in this study. Results. Our research has shown that diﬀerent brain functional outcomes, that is speed-accuracy motor control, inhibition response control and cognitive performance, risky-taking behaviour and impulsivity control, management of emotion, personality consciousness and physical activity have a common correlation with the increase in prefrontal cortex activity (measured by fNIRS) during Stroop test. Conclusion. Our studies have clearly shown that diﬀerent brain functional outcomes, that is speed-accuracy motor control, inhibition response control and cognitive performance, risky-taking behaviour and impulsivity control, management of emotion, personality consciousness and physical activity have a common correlation with the increase in prefrontal cortex activity (measured by fNIRS) during Stroop test. Considerable number of studies are needed to understand what is the functional essence of these relationships, but currently there is an increase of research establishing correlations between motor behaviour and cognition control. Keywords: prefrontal cortex, motor and cognitive control, impulsivity, risk-taking, moral decision making.